Valorisation of Phosphorus-Saturated Constructed Wetlands for the Production of Sugarcane - Mateus, Dina; Vaz, Mafalda; Pinho, Henrique (Journal of Technology Innovations in Renewable Energy, 2017)
Constructed wetlands (CW) are a clean and environmentally friendly alternative to conventional wastewater treatment methods, namely in the removal of the nutrients responsible for the eutrophication of receiving water bodies, as is the case of phosphorus compounds. The materials used as CW filling can directly contribute to the removal of phosphorus compounds from wastewater, but with the operating time they tend to become saturated and treatment efficiency decreases. In order to evaluate the viability of producing an energy crop in phosphorus-saturated CW, sugarcane growth was monitored in two pilot-scale CW filled with two different expanded clay aggregates used for 10 years in wastewater treatment. This paper presents the results obtained during the first year of plant development in the plant-cane cycle. Morphologic aspects of sugarcane growth, such as height and average diameter of stems, average leaf area and number of new sprouts, have been monitored. The results obtained are comparable with those cited in the literature for traditional cultivation. Dry biomass productivity of 26.6 ton per hectare per year can be achieved. Estimated sucrose productivity can reach 13.5 ton per hectare per year, and related bioethanol production potential can be between 2.4 and 7.6 cubic meters per hectare per year, depending on the CW filter media used. It is concluded that the cultivation of sugarcane in CW allows to extend the life of these systems by reusing fillers, and simultaneously is an alternative to produce bioethanol raw-material without the use of scarce resources such as arable land, fresh water and plant nutrients.